2016
DOI: 10.1164/rccm.201506-1247oc
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Antioxidants Augments the Acute Arterial Vasoconstriction Caused by Diesel Exhaust Inhalation

Abstract: Rationale: Diesel exhaust inhalation, which is the model trafficrelated air pollutant exposure, is associated with vascular dysfunction.Objectives: To determine whether healthy subjects exposed to diesel exhaust exhibit acute vasoconstriction and whether this effect could be modified by the use of antioxidants or by common variants in the angiotensin II type 1 receptor (AGTR1) and other candidate genes.Methods: In a genotype-stratified, double-blind, four-way crossover study, 21 healthy adult subjects were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Regrettably, these findings have not been replicated in human studies, with antioxidant-rich foods or supplements having inconsistent effects on PM 2.5 -induced heart rate variability (248,249) and vascular dysfunction (250252). Of concern, and despite the fact that in chronic smokers vitamin C has been shown to improve endothelium-dependent forearm blood flow (252), in another study, the vasoconstrictor effects of DE were actually greater in volunteers receiving vitamin C or NAC (253), These findings mirror those of the largely negative results of large-scale antioxidant trials for CVD in general (254), and may reflect the inability of current compounds to reach and reduce oxidative stress at key biological areas. Nevertheless, the identification of individuals with polymorphisms of antioxidant genes as being particularly susceptible to the effects of air pollution (210) suggests that this avenue of research still deserves further attention in hypothesis-driven studies with long-term intervention.…”
Section: Role Of Oxidative Stress In the Cardiovascular Effects Of Aimentioning
confidence: 99%
“…Regrettably, these findings have not been replicated in human studies, with antioxidant-rich foods or supplements having inconsistent effects on PM 2.5 -induced heart rate variability (248,249) and vascular dysfunction (250252). Of concern, and despite the fact that in chronic smokers vitamin C has been shown to improve endothelium-dependent forearm blood flow (252), in another study, the vasoconstrictor effects of DE were actually greater in volunteers receiving vitamin C or NAC (253), These findings mirror those of the largely negative results of large-scale antioxidant trials for CVD in general (254), and may reflect the inability of current compounds to reach and reduce oxidative stress at key biological areas. Nevertheless, the identification of individuals with polymorphisms of antioxidant genes as being particularly susceptible to the effects of air pollution (210) suggests that this avenue of research still deserves further attention in hypothesis-driven studies with long-term intervention.…”
Section: Role Of Oxidative Stress In the Cardiovascular Effects Of Aimentioning
confidence: 99%
“…Statins have been investigated in animal models and may attenuate the inflammatory effects of particulates, but evidence in humans is limited (43). Similarly, supplementation with dietary antioxidants has shown mixed results in attenuating the vascular effects of PM 2.5 and diesel exhaust exposure (44)(45)(46).…”
Section: Individual Measuresmentioning
confidence: 99%
“…In a second study of similar design, pre-treatment with vitamin C and N-acetylcysteine augmented DEP-induced vasoconstriction [198]. Both studies observed a role for genetic variability in dictating responses to DEP exposure and antioxidant supplementation [197,198].…”
Section: Background and Evidencementioning
confidence: 95%
“…In healthy participants, pre-treatment with N-acetylcysteine diminished DEP-induced airway responsiveness in participants with baseline airway hyperresponsiveness [197]. In a second study of similar design, pre-treatment with vitamin C and N-acetylcysteine augmented DEP-induced vasoconstriction [198]. Both studies observed a role for genetic variability in dictating responses to DEP exposure and antioxidant supplementation [197,198].…”
Section: Background and Evidencementioning
confidence: 99%